Globalisation, culture and social capital : library professionals on the move - O'Connor, Stephan (Library management ;, 2007)
Some library directors and other leading professionals in the field of library and information were asked to write about the experiences of taking on a job in another country than their native country. The papers are not academic in a narrow sense of the word, but they form a very coherent and reflective approach to national differences and it is evident that the authors have spent time to reflect on the consequences and effects of a job in another country - and in some cases on another continent. The results are presented in this issue of Library Management. It makes a very interesting read with quite some lessons.